Risk of fear and anxiety in utilising health app surveillance due to COVID-19: Gender differences analysis - Adi Alsyouf; Ra'ed Masa'deh; Moteb Albugami; Mohammad Al-Bsheish; Abdalwali Lutfi; Nizar Alsubahi (Risks, 2021)
Although technology trends and acceptance have been considered crucial topics, limited research has examined stress-specific factors such as health anxiety in the context of the COVID-19 pandemic based on people's attitudes toward a mobile health app using the Technology Acceptance Model (TAM). Accordingly, this study primarily highlights the psychological determinants stemming from the COVID-19 pandemic that affect the usage of a mobile health app. The study followed a cross-sectional design and adopted a snowball sampling technique to collect the data. The findings showed a significant association between perceived usefulness, perceived ease of use, and event-related fear and Tabaud App intention. The relationships between Tabaud App intention and COVID-19 anxiety on Tabaud App usage were also revealed. The study found a significant association between perceived ease of use and perceived usefulness. Additionally, the multi-group analysis showed that only two paths related to Tabaud App intention, perceived ease of use and perceived usefulness, differed significantly between males and females. Additionally, women experienced anxiety disorders more than men. The study contributes to the previous knowledge on the field by examining the psychological determinants resulting from the COVID-19 pandemic that influence using a mobile health app, namely, event-related fear and COVID-19 anxiety. The study results may help governments, health policymakers, and health organisations in Saudi Arabia contain the spread of the COVID-19 pandemic.
Keywords: 330; anxiety; COVID-19 pandemic; event-related fear; mHealth; Saudi Arabia; TAM